Resistência de união de sistemas adesivos em dentina previamente exposta a materiais contendo eugenol - Rosa, Lucas Saldanha da (2020)
Zinc oxide-eugenol cement (ZOE) is still a reality in clinical practice. Eugenol present in cement affects the polymerization of monomers, such as those found in adhesive systems. Previous studies have shown divergence regarding the influence of the effect of eugenol over time on the bond strength (BS) of adhesive systems, with none evaluating times longer than 45 days. Two studies are presented evaluating the effects of cement with ZOE in the BS of adhesive systems. The first of them is a systematic review and meta-analysis on the influence of temporary eugenol-based materials on adhesive systems bond strength to dentin. Searches were performed in the PubMed, Web of Science and Scopus databases without limitation of year or language, resulting in 603 potential studies, which met inclusion and exclusion criteria. Of the 35 full-text read, 27 were elected for systematic review and 26 for meta-analysis. After selection, data extraction and definition of risk of bias, the meta-analysis was performed using inverted variance and a random effects model (p <0.05). Heterogeneity was verified with Cochran Q and I2 tests. Temporary eugenol-based materials were statistically associated with lower BS values. Subgroup analyzes also showed the same effects after 24 hours and 7 days, as well as when divided into resin cements, total-etching adhesive systems and self-etching adhesive systems. Times between 14 and 45 days showed no differences. Laboratory evidence suggests that there is a decrease in the BS to dentin of adhesives systems exposed to ZOE cements up to one week, regardless of the strategy used. The second research have the objective of evaluating the micro shear bond strength(μSBS) of an adhesive system to dentin previously provisionally restored with ZOE cement during different times. Sixty-four healthy bovine incisors had their dentin surfaces exposed and were divided into 8 groups (n = 8), with the groups 24 hours, 7, 15, 30, 60, 120 and 180 days provisionally restored with ZOE cement for the corresponding times, another control group without provisional restorations. After the mechanical removal of the ZOE cement and cleaning of the surfaces, an adhesive system of total conditioning was applied and cylinders of composite resin were made for μSBS test. Failure analysis was performed using a stereomicroscope and data analysis was performed using Kruskal Wallis and Dunn's post hoc test (5% significance). Lower RU values were found in the experimental groups 24h, 7, 15 and 30d. when compared to the control (p <0.05). Similar μSBS values were found between groups 60, 120, 180d and control. ZOE cements impair the bond strength of total acid conditioning adhesive systems for up to 30 days. In 60 days, it is already safe to perform restorations with resinous materials. It was concluded that ZOE cements reduce the BS of adhesive systems to up to 30 days, with a critical period up to 7 days.